ANALYSIS AND PREDICTION OF TOMATO PRICE IN SERBIA - Ivanišević, Dragan; Mutavdžić, Beba; Novković, Nebojša; Vukelić, Nataša (Economics of Agriculture, 2015)
Tomato is one of the most important vegetable crops in Serbia. The average annual production of tomato has been about 174,000 tones. The topic of this research paper is the analysis of the changes and the future tendencies of the price parameters of tomato in Serbia, with the aim to forecast the real, absolute and relative (the parity with wheat) tomato price, i.e. to forecast the economic conditions for the production. The analysis of the time series (1994-2010) has been done by means of descriptive statistics, and the suitable ARIMA models were used for the forecast (2011-2015). The average real tomato price in the period 1994-2010 was 0.17 EUR/kg, and the average parity price for tomato/wheat was 1.5. The tendencies for the real growth of tomato price as well as the increase in the parity price with wheat were noticed during the analyzed period. A further real growth of tomato price and the growth of the parity with wheat have been predicted for the forecast period. This means that both absolute and relative price conditions in tomato production have been improving. The predicted tomato price in 2015 is 0.22 EUR/kg, and the parity price with wheat is 2.88, which is considerably higher than the average in the observed time period. The models for the forecast indicated that the previous years tomato price, i.e. parity, has a considerable influence over the formation of tomato price and the establishing of the parity with wheat.